A meta-analysis of water quality and aquatic macrophyte responses in 18 lakes treated with lanthanum modified bentonite (Phoslock®). (15th June 2016) - Spears, Bryan M.; Mackay, Eleanor B.; Yasseri, Said; Gunn, Iain D.M.; Waters, Kate E.; Andrews, Christopher; Cole, Stephanie; De Ville, Mitzi; Kelly, Andrea; Meis, Sebastian; Moore, Alanna L.; Nürnberg, Gertrud K.; et al.
Abstract: Lanthanum (La) modified bentonite is being increasingly used as a geo-engineering tool for the control of phosphorus (P) release from lake bed sediments to overlying waters. However, little is known about its effectiveness in controlling P across a wide range of lake conditions or of its potential to promote rapid ecological recovery. We combined data from 18 treated lakes to examine the lake population responses in the 24 months following La-bentonite application (range of La-bentonite loads: 1.4–6.7 tonnes ha −1 ) in concentrations of surface water total phosphorus (TP; data available from 15 lakes), soluble reactive phosphorus (SRP; 14 lakes), and chlorophyll a (15 lakes), and in Secchi disk depths (15 lakes), aquatic macrophyte species numbers (6 lakes) and aquatic macrophyte maximum colonisation depths (4 lakes) across the treated lakes. Data availability varied across the lakes and variables, and in general monitoring was more frequent closer to the application dates. Median annual TP concentrations decreased significantly across the lakes, following the La-bentonite applications (from 0.08 mg L −1 in the 24 months pre-application to 0.03 mg L −1 in the 24 months post-application), particularly in autumn (0.08 mg L −1 to 0.03 mg L −1 ) and winter (0.08 mg L −1 to 0.02 mg L −1 ). Significant decreases in SRP concentrations over annual (0.019 mg L −1 to 0.005 mg L −1 ), summer (0.018 mg L −1 to 0.004 mg L −1 ), autumn (0.019 mg L −1 to 0.005 mg L −1 ) and winter (0.033 mg L −1 to 0.005 mg L −1 ) periods were also reported. P concentrations following La-bentonite application varied across the lakes and were correlated positively with dissolved organic carbon concentrations. Relatively weak, but significant responses were reported for summer chlorophyll a concentrations and Secchi disk depths following La-bentonite applications, the 75th percentile values decreasing from 119 μg L −1 to 74 μg L −1 and increasing from 398 cm to 506 cm, respectively. Aquatic macrophyte species numbers and maximum colonisation depths increased following La-bentonite application from a median of 5.5 species to 7.0 species and a median of 1.8 m to 2.5 m, respectively. The aquatic macrophyte responses varied significantly between lakes. La-bentonite application resulted in a general improvement in water quality leading to an improvement in the aquatic macrophyte community within 24 months. However, because, the responses were highly site-specific, we stress the need for comprehensive pre- and post-application assessments of processes driving ecological structure and function in candidate lakes to inform future use of this and similar products. Highlights: Water quality and macrophyte community responses were assessed following Phoslock treatments. Phosphorus concentration and phytoplankton biomass decreased and water clarity increased. Macrophyte species richness and extent increased. Responses were highly site specific and decreased with increasing DOC concentrations.